Evolutionary engineering and molecular characterization of cobalt-resistant Rhodobacter sphaeroides - Atay, Güneş; Holyavkin, Can; Can, Hanay; Arslan, Mevlüt; Topaloğlu, Alican; Trotta, Massimo; Çakar, Zeynep Petek (Frontiers in Microbiology, 2024)
With its versatile metabolism including aerobic and anaerobic respiration, photosynthesis, photofermentation and nitrogen fixation, Rhodobacter sphaeroides can adapt to diverse environmental and nutritional conditions, including the presence of various stressors such as heavy metals. Thus, it is an important microorganism to study the molecular mechanisms of bacterial stress response and resistance, and to be used as a microbial cell factory for biotechnological applications or bioremediation. In this study, a highly cobalt-resistant and genetically stable R. sphaeroides strain was obtained by evolutionary engineering, also known as adaptive laboratory evolution (ALE), a powerful strategy to improve and characterize genetically complex, desired microbial phenotypes, such as stress resistance. For this purpose, successive batch selection was performed in the presence of gradually increased cobalt stress levels between 0.1-15 mM CoCl2 for 64 passages and without any mutagenesis of the initial population prior to selection. The mutant individuals were randomly chosen from the last population and analyzed in detail. Among these, a highly cobalt-resistant and genetically stable evolved strain called G7 showed significant cross-resistance against various stressors such as iron, magnesium, nickel, aluminum, and NaCl. Growth profiles and flame atomic absorption spectrometry analysis results revealed that in the presence of 4 mM CoCl2 that significantly inhibited growth of the reference strain, the growth of the evolved strain was unaffected, and higher levels of cobalt ions were associated with G7 cells than the reference strain. This may imply that cobalt ions accumulated in or on G7 cells, indicating the potential of G7 for cobalt bioremediation. Whole genome sequencing of the evolved strain identified 23 single nucleotide polymorphisms in various genes that are associated with transcriptional regulators, NifB family-FeMo cofactor biosynthesis, putative virulence factors, TRAP-T family transporter, sodium/proton antiporter, and also in genes with unknown functions, which may have a potential role in the cobalt resistance of R. sphaeroides.